GEREJA YANG BERBAGI DAYA DALAM MISI LINTAS BUDAYA: KAJIAN MISIOLOGIS ROMA 15:22-33 - Prabowo, Paulus Dimas; Kalaka, Jhon (Manna Rafflesia, 2023)
The church has been chosen as God’s mission agent in the time of grace to express God’s love for all ethnic groups in the world in a cross-cultural mission program. However, church mission activities (missio ecclesiae) in cross-cultural missions are often interpreted as limited to preaching the gospel by taking Matthew 28:19-20 to be the primary text reference. Evangelicals and Pentecostals widely hold this view. Considering other texts, it will be evident that the local church’s involvement in cross-cultural missions is more expansive to include other activities. Through the method of thematic analysis of Romans 15:22-33, through a missiological lens, it is revealed that the church can share power in cross-cultural missions in three ways: accompanying evangelism in the field and donating funds for humanitarian services and praying for ongoing tasks. Church involvement is holistic, touching both spiritual and physical aspects.